LiNbO3 / LiTaO3 piezoelectric coating sensor and preparation method
By adopting LiNbO3/LiTaO3 nanocomposite piezoelectric coating and gradient multi-layer structure design, the problems of existing piezoelectric coating falling off and structural deterioration in high-temperature environments are solved, and high-reliability piezoelectric sensing in high-temperature and radiation environments are achieved.
Patent Information
- Application Number
- CN202210624331.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The existing piezoelectric coatings have problems such as shedding and inter-diffusion of elements in high-temperature environments, which are difficult to meet the industrial application needs in high-temperature and radiation environments.
LiNbO3/LiTaO3 nanocomposite piezoelectric coating is adopted, and the gradient multi-layer structure design includes Cr binding layer, AlN high-temperature diffusion barrier layer, LiNbO3/LiTaO3 nano multi-layer piezoelectric functional layer, Cr protection layer, Ag/Cr transition layer and Ag electrode layer to improve the density, wear resistance and radiation resistance of the coating.
It realizes high-reliability piezoelectric sensing in high-temperature and radiation environments, reduces the risk of peeling of the coating when the high and low temperatures alternate, improves radiation and corrosion resistance, and is suitable for high-temperature environments of 1000-1200℃.
Smart Images

Figure CN115184453B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric coating preparation, and in particular to a LiNbO3 / LiTaO3 piezoelectric coating sensor and a preparation method thereof. Background Art
[0002] Nondestructive testing (NDT) is widely used in industry to detect small defects in the early stage before fatal failure. Various NDT methods have been developed, and ultrasonic technology with piezoelectric ultrasonic sensors (UTs) is one of the commonly used methods. Due to its underground detection capability, simplicity and cost-effectiveness, it can measure the thinning degree of the structure and detect defects and cracks inside the structure. It has been widely used in nondestructive testing (NDT) of metal structures, such as fuselages, engines, pipelines, and structural components of nuclear power plants. Many of these applications, such as corrosion, erosion, and defect detection, occur at high temperatures (600°C). Some industrial applications require higher temperatures, such as 1000-1200°C in reactors, with nuclear radiation up to 10 20 n / cm 2 Therefore, there is a strong demand for radiation-resistant and high-temperature-resistant ultrasonic sensors.
[0003] Thin films with piezoelectric effect are very suitable for defect and preload detection. By depositing a coating with excellent ultrasonic excitation performance directly on the surface of the detected object, a permanent follow-up sensor of the detected object can be obtained.
[0004] The most mature one at present is lead zirconate titanate PZT piezoelectric ceramic, which is the piezoelectric material with the best piezoelectric sensing performance in the low temperature field. However, the Curie temperature limits its application in high temperature. Later, lead titanate (PbTiO3) and bismuth titanate (Bi4Ti3O 12 ), alumina (ZnO), etc. were introduced one after another, but their temperature resistance was still not ideal. They could only be used in working environments below 400°C and could not meet the requirements of industrial sites with higher temperatures. Later, researchers used sol-gel spraying technology to develop LiNbO3 / PZT, LiNbO3(LN) / Bi4Ti3O 12 (BiT) and other composite thick ceramic (greater than 40μm) film piezoelectric materials have further improved the ultrasonic sensing performance and thermal stability, proving the feasibility and excellence of composite materials. However, the sol-gel spraying technology is time-consuming and requires post-processing processes such as drying, which makes it unsuitable for industrial production.
[0005] Therefore, it is necessary to improve the existing technology and develop new piezoelectric coatings that are resistant to high temperature, corrosion and radiation.
[0006] LiNbO3 has the advantages of high operating temperature (1110℃) and large d33 value (~39pC / N), and excellent radiation resistance. LiTaO3 is a tantalum analogue of LiNbO3, and has many of the same properties as LiNbO3, such as both are trigonal, piezoelectric, melting point up to 1650℃, not prone to depolarization, low dielectric loss, good electromechanical coupling, temperature coefficient and other excellent properties. The present invention innovatively proposes to compound LiNbO3 with LiTaO3 to prepare a LiNbO3 / LiTaO3 multilayer composite coating to achieve more effective mechanical energy-electrical energy conversion, thereby improving the piezoelectric constant of the material and obtaining better acoustic properties. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion-resistant and radiation-resistant fasteners and a preparation method thereof.
[0008] The technical solution of the present invention is as follows:
[0009] One of the purposes of the present invention is to provide a LiNbO3 / LiTaO3 piezoelectric coating sensor and a preparation method, namely, a high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion-resistant and radiation-resistant fasteners, the main body of which is a LiNbO3 / LiTaO3 nanocomposite piezoelectric coating, which inhibits the growth of LiTaO3 and LiNbO3 columnar crystals, improves the density of the piezoelectric coating, and the wear resistance and corrosion resistance of the coating.
[0010] The second object of the present invention is to provide a method for preparing a high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion-resistant and radiation-resistant fasteners. The preparation process is simple, easy to adjust, industrial production batches are easy to achieve, the processing efficiency is high, and the production cost of the manufacturer can be greatly reduced.
[0011] To achieve the above object, the technical solution of the present invention is as follows:
[0012] In the first aspect, the present invention provides a LiNbO3 / LiTaO3 piezoelectric coating sensor, characterized in that it includes a LiNbO3 / LiTaO3 nanocomposite piezoelectric coating; the LiNbO3 / LiTaO3 nanocomposite piezoelectric coating adopts a gradient multilayer structure, and includes, from the inside to the outside, a bonding layer, a high-temperature diffusion barrier layer, a piezoelectric functional layer, a protective layer, a transition layer and an electrode layer; wherein the bonding layer is a pure metal Cr layer, the high-temperature diffusion barrier layer is an AlN layer, the piezoelectric functional layer is a LiNbO3 / LiTaO3 nanomultilayer film, the protective layer is a Cr layer, the transition layer is an Ag / Cr layer, and the electrode layer is Ag.
[0013] As a preferred solution, the high temperature resistant LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor for fasteners has a total thickness of 25-70 microns and includes an Ag electrode layer.
[0014] Further, the thickness of the Cr bonding layer is 0.5-1 micrometer;
[0015] The thickness of the AlN layer high temperature diffusion barrier layer is 3-5 microns;
[0016] The thickness of the piezoelectric functional layer is 10-20 microns, and the piezoelectric functional layer is a c-axis oriented LiNbO3 / LiTaO3 nano-multilayer film, wherein the thickness of the LiNbO3 single layer is 0.5-2 microns, the thickness of the LiTaO3 single layer is 0.5-2 microns, the modulation period is 1-4 microns, and the number of LiNbO3 / LiTaO3 layers is between 5-20;
[0017] The thickness of the Cr electrode bonding layer / protective layer is 0.5-20 microns;
[0018] The thickness of the Ag / Cr transition layer is 1-2 microns;
[0019] The thickness of the Ag electrode layer is 10-20 microns.
[0020] In a second aspect, the present invention provides a method for preparing a high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for a corrosion-resistant and radiation-resistant fastener as described above, characterized in that it comprises the following steps:
[0021] S1: Plasma cleaning substrate: using 99.99% pure Cr target, adjusting the target fastener spacing between 100-200mm, in 25-300℃, 0.5-2Pa argon environment, substrate bias 100-200V, duty cycle 40-90%, cathode current 80-150A, plasma etching the fastener surface, etching time 5-20 minutes;
[0022] S2: Deposition of Cr bonding layer: After etching, use a 99.99% pure Cr target, adjust the target fastener spacing between 40-100 mm, set the power supply power between 500-1000 W, and deposit a Cr bonding layer on the fastener surface in an argon environment of 25-300 ° C and 0.5-3 Pa for 5-20 minutes;
[0023] S3: Deposition of AlN high temperature diffusion barrier layer: After the deposition of the Cr bonding layer, a 99.99% pure Al target is used, the target fastener spacing is adjusted to 40-100 mm, the power supply is set to 500-1000 W, the sample preparation room temperature is set to 100-300 ° C, 1.5-4 Pa Ar, N2 mixed gas is introduced, and the Ar / N2 ratio is between 0.1-9, and the AlN high temperature diffusion barrier layer is deposited on the surface of the Cr bonding layer for 200-300 minutes;
[0024] S4: Deposition of LiNbO3 / LiTaO3 piezoelectric functional layer: After the AlN layer is deposited, a 99.99% pure LiTaO3 target and a LiNbO3 target are used, the target fastener spacing is adjusted to be between 40-100 mm, the power supply is set to be between 500-1000 W, and the sample preparation room temperature is set to be between 150-300° C., and a LiNbO3 / LiTaO3 piezoelectric functional layer is deposited on the surface of the AlN layer;
[0025] S5: Deposition of Cr electrode bonding layer / protective layer: After the deposition of the LiNbO3 / LiTaO3 piezoelectric functional layer, a 99.99% pure Cr target is used, the target fastener spacing is adjusted to be between 40-100 mm, the power supply power is set to be between 500-1000 W, and the Cr electrode bonding layer / protective layer is deposited on the surface of LiNbO3 / LiTaO3 in an argon environment of 25-300°C and 0.5-3Pa for 5-240 minutes;
[0026] S6: Deposition of Ag / Cr transition layer: After the deposition of the Cr electrode bonding layer / protective layer, a AgCr mixed target is used, with a ratio of Ag to Cr between 1:5 and 5:1, the target fastener spacing is adjusted between 40-100mm, and the power supply is set between 500-1000W. In an argon environment of 25-300℃ and 0.5-3Pa, an Ag / Cr transition layer is deposited on the surface of the Cr layer for 5-20 minutes;
[0027] S7: Deposition of Ag electrode layer: After the deposition of the Ag / Cr transition layer, a 99.99% pure Ag target is used, the target fastener spacing is adjusted to be between 30-60 mm, the power supply power is set to be between 500-1000 W, and the Ag electrode layer is deposited on the surface of the Ag / Cr transition layer in an argon environment of 25-300°C and 0.5-3Pa for 30-90 minutes;
[0028] S8: After the preparation is completed, it is naturally cooled to obtain a high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion-resistant and radiation-resistant fasteners.
[0029] As a preferred embodiment, in step S1, the substrate includes an experimental substrate and an industrial substrate. The experimental substrate is a single crystal silicon wafer or a stainless steel wafer, which is used to characterize the coating thickness, crystal structure, elemental composition and coating bonding strength; the industrial substrate is a Ti6Al4V titanium alloy bolt, an Inconel 718 bolt, a stainless steel bolt, and a nut, a stud, a screw, a washer, a pin, a rivet, and a welding nail, which is used to measure ultrasonic signals and test the piezoelectric properties, high temperature stability, corrosion and radiation resistance of the coating in actual applications.
[0030] Furthermore, in step S4, after the deposition of the AlN high-temperature diffusion barrier layer is completed, the LiTaO3 target and the LiNbO3 target are turned on at the same time, and a 1.5-4Pa Ar and O2 mixed gas is introduced, and the Ar / O2 ratio is between 0.1-9; when the fastener rotates in front of the LiTaO3 target, it stays for 30-90 minutes to form a LiTaO3 coating; when the fastener rotates in front of the LiNbO3 target, it stays for 30-90 minutes to form a LiNbO3 coating, and the fastener rotates continuously to form 5-20 pairs of LiNbO3 / LiTaO3 coatings on its surface to prepare a nano-multilayer composite piezoelectric functional coating.
[0031] Furthermore, after the deposition of the AlN high-temperature diffusion barrier layer is completed, the LiTaO3 coating is deposited first, and then the LiNbO3 coating is deposited. The outermost layer of the LiNbO3 / LiTaO3 nanocomposite piezoelectric coating is also LiNbO3; the LiNbO3 coating is located on the surface, and uses its own oxide characteristics to protect the piezoelectric coating from oxidation, thereby improving its high-temperature stability and its radiation resistance, and enhancing the coating's ability to resist protons and gamma radiation.
[0032] The working principle of the present invention is as follows:
[0033] The piezoelectric nanocomposite coating of the present invention adopts a gradient multilayer structure, and is provided with a pure metal Cr bonding layer, an AlN high temperature diffusion barrier layer, a LiNbO3 / LiTaO3 nano multilayer piezoelectric functional layer, a Cr protective layer, an Ag / Cr transition layer, and an Ag electrode layer, each layer performs its own function, so that the coating has piezoelectric performance, high temperature resistance, radiation resistance, and radiation resistance. The gradient multilayer structure reduces the difference in composition between the piezoelectric nanocomposite coating material and the steel substrate of the fastener, reduces the internal stress of the coating, and avoids peeling due to the difference in expansion coefficient during high and low temperature impact. The main reason for using LiTaO3 and LiNbO3 piezoelectric coating composite is that both are trigonal crystals with the same structure, which is conducive to the growth of multilayer coatings with uninterrupted columnar structures. In addition, the two have excellent and complementary performances. LiNbO3 has the advantages of high operating temperature (1110℃( and large d33 value (~39pC / N(), and excellent radiation resistance. LiTaO3 is also piezoelectric, with a melting point of up to 1650℃, is not prone to depolarization, has low dielectric loss, and has excellent electromechanical coupling, temperature coefficient and other excellent properties. The multilayer structure is used to release the internal stress of the coating and improve the coating's crack resistance under high temperature creep and deformation conditions. At the same time, even if the surface LiNbO3 / LiTaO3 multilayer film is partially cracked or damaged, the LiNbO3 / LiTaO3 layer below it will quickly form a dense oxide protective film at the crack site to avoid further development of corrosion and achieve a self-healing effect.
[0034] The present invention aims to overcome the shortcomings of the existing piezoelectric coatings that are easy to fall off due to alternating high and low temperatures and that the elements diffuse mutually in high temperature environments, resulting in structural degradation. The gradient structure and nano multilayer structure are used to reduce the stress of the coating and improve the fatigue resistance. In particular, the metal Cr bonding layer and the AlN high temperature diffusion barrier layer provide good adhesion performance for the piezoelectric functional layer, effectively reducing the risk of coating peeling off during hot and cold cycles and the diffusion of elements at high temperatures. In order to improve the adhesion, before depositing the coating, the present invention sets a substrate bias and uses an energy-carrying plasma etching technology to remove oxides, oil stains, dust and other contaminants on the surface of the substrate. This process can clean the substrate, improve the adhesion of the piezoelectric coating, prevent oxides and oil stains on the surface of the fasteners from destroying the bonding between the coating and the substrate, and prevent the coating from peeling off during high temperature heating and rapid cooling. Dust will cause uneven coating, forming bulges and interlayer disorder. After the bulges fall off, holes will be left on the coating, destroying the transmission of ultrasonic stress.
[0035] The second purpose of the present invention is to overcome the stress corrosion problem of piezoelectric coatings for fasteners. A Cr protective layer is deposited on the surface of the LiNbO3 / LiTaO3 piezoelectric composite coating. Cr can not only serve as a bonding transition layer between the piezoelectric coating and the Ag electrode to improve adhesion, but Cr is also a corrosion-resistant element that can form a dense passivation film, reduce the sensitivity of the coating to corrosive ions such as Cl, and improve the pitting corrosion resistance of the coating.
[0036] The third aspect of the present invention is to overcome the problem of radiation damage to piezoelectric coatings for fasteners. A layer of AlN is deposited between the LiNbO3 / LiTaO3 piezoelectric composite coating and the substrate. AlN not only serves as a diffusion barrier layer to improve the high-temperature element stability of the coating, but also has excellent radiation resistance, which can improve the coating's ability to resist protons and gamma radiation. In addition, the piezoelectric coating body adopts LiNbO3 coating, and the LiNbO3 pulse response and transmission coefficient have excellent radiation stability, which overcomes the problem of radiation damage to piezoelectric coatings for fasteners.
[0037] In the technical solution of the present invention, the key points are as follows in combination with the principle:
[0038] The above-mentioned LiNbO3 / LiTaO3 nanocomposite piezoelectric coating adopts a gradient layer structure, which includes a bonding layer, a high-temperature diffusion barrier layer, a piezoelectric functional layer, a protective layer, a transition layer and an electrode layer from the inside to the outside, wherein the bonding layer is a pure metal Cr layer, the high-temperature diffusion barrier layer is an AlN layer, the piezoelectric functional layer is a LiNbO3 / LiTaO3 nano multilayer film, the protective layer is a Cr layer, the transition layer is an Ag / Cr layer, and the electrode layer is Ag. The total thickness of the LiNbO3 / LiTaO3 nanocomposite piezoelectric coating for high-temperature and radiation-resistant fasteners is 25-70 microns.
[0039] The thickness of the Cr bonding layer is 0.5-1 micron. Cr metal has good compatibility with fastener substrates such as bolts, and Cr is used as a bonding transition layer between the bolt and the piezoelectric coating, and between the piezoelectric coating and the Ag electrode to improve the adhesion between the coating and the substrate.
[0040] The thickness of the AlN high temperature diffusion barrier layer is 3-5 microns, which improves the high temperature element stability of the coating and has excellent radiation resistance, and can improve the coating's ability to resist protons and gamma radiation.
[0041] The thickness of the piezoelectric functional layer is 10-20 microns. The piezoelectric functional layer is a c-axis oriented LiNbO3 / LiTaO3 nano-multilayer film, wherein the thickness of the LiTaO3 single layer is 0.5-2 microns, and the modulation period is 1-4 microns. LiNbO3 improves the coating's ability to resist proton and γ radiation and improves its high-temperature stability; the LiNbO3 / LiTaO3 composite has good piezoelectric properties and realizes stress detection.
[0042] The thickness of the Cr protective layer is 0.5-20 microns. Cr is a corrosion-resistant element that can form a dense passivation film, reduce the sensitivity of corrosive ions such as Cl, and improve the pitting corrosion resistance of the coating.
[0043] The thickness of the Ag / Cr transition layer is 1-2 microns. The Cr / Ag transition layer is used to improve the adhesion between the Cr bonding layer and the Ag electrode layer.
[0044] The thickness of the Ag electrode layer is 10-20 microns. Silver has high temperature oxidation resistance, and as a high-density metal, silver is suitable for use as an acoustic matching layer to improve the sensitivity and bandwidth of the sensor.
[0045] In the above step S1, the substrate includes an experimental substrate and an industrial substrate. The experimental substrate is a single crystal silicon wafer, a stainless steel sheet, etc., which is used to characterize the coating thickness, crystal structure, element composition, coating bonding strength, etc., and provide a reference for industrial applications. The industrial substrate is mainly a fastener such as a bolt (Ti6Al4V titanium alloy bolt, chromium-nickel-inconel alloy 718 bolt, etc.), which is used to measure ultrasonic signals and test the piezoelectric properties, high temperature stability, corrosion and radiation resistance of the coating;
[0046] In the above step S4, after the deposition of the AlN high-temperature diffusion barrier layer is completed, the LiTaO3 target and the LiNbO3 target are turned on at the same time, and a 1.5-4Pa Ar and O2 mixed gas is introduced, and the Ar / O2 ratio is between 0.1-9. When the fastener rotates in front of the LiTaO3 target, it stays for 30-90 minutes to form a LiTaO3 coating. When the fastener rotates in front of the LiNbO3 target, it stays for 30-90 minutes to form a LiNbO3 coating. The fastener rotates continuously to form 5-20 pairs of LiNbO3 / LiTaO3 coatings on its surface to prepare a nano-multilayer piezoelectric functional coating.
[0047] After the AlN high-temperature diffusion barrier layer is deposited, the LiTaO3 coating is deposited first, and then the LiNbO3 coating is deposited. The outermost layer of the LiNbO3 / LiTaO3 nanocomposite piezoelectric coating is also LiNbO3. The LiNbO3 coating is located on the surface, and uses its own oxide characteristics to protect the piezoelectric coating from oxidation, improve its high-temperature stability, and its radiation resistance, and enhance the coating's ability to resist protons and γ radiation.
[0048] The present invention has the following advantages and beneficial effects:
[0049] 1. The present invention is the first to composite LiTaO3 piezoelectric coating and LiNbO3 piezoelectric coating to construct a nano-multilayer piezoelectric coating, so that the coating has better hardness, wear resistance and toughness than conventional piezoelectric coatings. LiNbO3 improves the coating's ability to resist proton and γ radiation. At the same time, LiNbO3 and LiTaO3 piezoelectric coatings themselves are oxides, and there is no need to deposit an additional oxide protective layer. The piezoelectric coating can be well protected from oxidation at high temperatures, thereby improving its high-temperature stability. LiTaO3 and LiNbO3 have the same structure and both have excellent piezoelectric properties. The combination of the two will further promote the piezoelectric effect and realize fastener stress detection.
[0050] 2. The present invention deposits AlN and Cr coatings between the piezoelectric composite coating and the substrate. AlN inhibits the diffusion of Cr elements into the LiNbO3 / LiTaO3 piezoelectric composite coating, thereby improving the high-temperature element stability and radiation resistance of the coating. Cr improves the adhesion between the coating and the substrate.
[0051] 3. The present invention deposits an Ag electrode layer on the outermost surface of the entire coating. Ag has high-temperature oxidation resistance. At the same time, silver, as a high-density metal, is suitable for use as an acoustic matching layer to improve the sensitivity and bandwidth of the sensor, forming a smart bolt that can be measured in situ online throughout its entire life cycle.
[0052] 3. The present invention deposits a Cr coating on the surface of the piezoelectric composite coating as a protective layer and a bonding layer. Cr can form a dense passivation film, reduce the sensitivity of corrosive ions, improve the pitting corrosion resistance of the coating, and at the same time improve the bonding force between the electrode layer and the piezoelectric layer.
[0053] 4. The present invention deposits the Ag / Cr transition layer between the Ag electrode layer and the Cr bonding layer to improve the adhesion between the Cr bonding layer and the Ag electrode layer.
[0054] 5. The present invention makes full use of gradient structure and nano multilayer structure to form a gradual composition, reduce the stress between the coating and the substrate, and improve adhesion. Compared with conventional piezoelectric coating materials, the present invention uses multilayer structure technology to inhibit the coarsening of LiTaO3 and LiNbO3 columnar crystals and promote the densification of the piezoelectric coating, which can improve the mechanical energy-electric energy conversion sensitivity of the coating, thereby improving the piezoelectric constant of the material and obtaining better acoustic properties.
[0055] 6. The present invention adopts radio frequency magnetron sputtering coating technology to prepare LiNbO3 / LiTaO3 piezoelectric composite coating. Compared with sol-gel spraying technology, it not only has a fast deposition rate, low cost, and no need for post-processing processes such as drying, but is also suitable for industrial mass production. At the same time, it has better crystallization and bonding properties and wide adaptability, and can be extended to other functional coatings and material fields besides piezoelectric coatings.
[0056] 7. The present invention can obtain LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensors with different high temperature stability, corrosion resistance and radiation resistance by regulating the target substrate distance, power supply power, sample preparation temperature, ambient gas type, air pressure, sample preparation time, modulation cycle, number of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating layers, etc. If the working requirements of the corrosive environment need to be met, the Cr protective layer can be appropriately thickened, and if the working environment needs to be high temperature or radiation, the top layer of LiNbO3 piezoelectric coating can be appropriately thickened.
[0057] 8. The LiNbO3 / LiTaO3 composite piezoelectric coating for smart fasteners prepared by the present invention has the characteristics of high temperature resistance, radiation resistance, radiation resistance and high bonding strength. It can work for a long time with high reliability in high temperature, high radiation and corrosive industrial sites. A permanent follow-up ultrasonic detection thin film sensor can be customized for the bolts to form a smart bolt that can be measured in situ online throughout its life cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Schematic diagram of the coating structure designed for the present invention.
[0059] Figure 2 It is the ultrasonic signal before and after the piezoelectric coating corrosion in Example 2.
[0060] Figure 3 These are the ultrasonic signals of the piezoelectric coating in Example 3 before and after high-temperature annealing.
[0061] Figure 1 In: 1. Substrate; 2. Cr bonding layer; 3. AlN high-temperature diffusion barrier layer; 4. LiNbO3 / LiTaO3 composite piezoelectric coating; 5. Cr electrode bonding layer / protective layer; 6. Ag / Cr transition layer; 7. Ag electrode layer.
[0062] Figure 2 Middle: 8. Ultrasonic signal of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating before corrosion; 9. Ultrasonic signal of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating after corrosion. DETAILED DESCRIPTION
[0063] For a better understanding of the present invention, the technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0064] Example 1
[0065] The preparation method of the high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion-resistant and radiation-resistant fasteners in this embodiment comprises the following steps:
[0066] S1: Plasma beam cleaning substrate: using 99.99% pure Cr target, adjusting the target substrate spacing between 100-200mm, in 25-300℃, 0.5-2Pa argon environment, substrate bias 100-200V, duty cycle 40-90%, cathode current 80-150A, plasma etching the substrate surface, etching time 5-20 minutes;
[0067] S2: Deposition of Cr bonding layer: After etching, use a 99.99% pure Cr target, adjust the target-substrate distance between 40-100 mm, set the power between 500-1000 W, and deposit a 0.5-1 μm thick Cr bonding layer on the substrate surface in an argon environment of 25-300°C and 0.5-3 Pa for 5-20 minutes;
[0068] S3: Deposition of AlN high temperature diffusion barrier layer: After the deposition of the Cr bonding layer, a 99.99% pure Al target is used, the target substrate spacing is adjusted to 40-100 mm, the power supply is set to 500-1000 W, the sample preparation room temperature is set to 100-300 ° C, 1.5-4 Pa Ar, N2 mixed gas is introduced, and the Ar / N2 ratio is between 0.1-9, and a 3-5 μm thick AlN high temperature diffusion barrier layer is deposited on the surface of the Cr bonding layer for 200-300 minutes;
[0069] S4: Deposition of LiNbO3 / LiTaO3 piezoelectric functional layer: After the deposition of AlN high temperature diffusion barrier layer, 99.99% pure LiTaO3 target and LiNbO3 target are used, the target substrate distance is adjusted to be between 40-100mm, the power supply is set to be between 500-1000W, the sample preparation room temperature is set to be between 150-300℃, 1.5-4Pa Ar, O2 mixed gas is introduced, and the Ar / O2 ratio is between 0.1-9. When the substrate is rotated to the front of the LiTaO3 target, the residence time is 30-90 minutes to form a LiTaO3 coating, and when the substrate is rotated to the front of the LiNbO3 target, the residence time is 30-90 minutes to form a LiNbO3 coating. The fastener is rotated continuously to deposit 5-20 pairs of LiNbO3 / LiTaO3 coatings on the surface of the AlN layer to prepare a nano multilayer piezoelectric functional coating with a total thickness of 10-20 microns;
[0070] S5: Deposition of Cr electrode bonding layer / protective layer: After the deposition of the LiNbO3 / LiTaO3 piezoelectric functional layer, a 99.99% pure Cr target is used, the target substrate spacing is adjusted to be between 40-100 mm, the power supply is set to be between 500-1000 W, and a 0.5-20 μm thick Cr electrode bonding layer / protective layer is deposited on the surface of LiNbO3 / LiTaO3 in an argon environment at 25-300°C and 0.5-3Pa for 5-240 minutes;
[0071] S6: Deposition of Ag / Cr transition layer: After the deposition of the Cr electrode bonding layer / protective layer, a AgCr mixed target is used, the ratio of Ag to Cr is between 1:5 and 5:1, the target substrate spacing is adjusted to be between 40-100mm, and the power supply is set to be between 500-1000W. In an argon environment of 25-300℃ and 0.5-3Pa, a 1-2 micron thick Ag / Cr transition layer is deposited on the surface of the Cr layer for 5-20 minutes;
[0072] S7: Deposition of Ag electrode layer: After the deposition of the Ag / Cr transition layer, a 99.99% pure Ag target is used, the target substrate spacing is adjusted to be between 30-60 mm, the power supply is set to be between 500-1000 W, and a 10-20 μm thick Ag electrode layer is deposited on the surface of the Ag / Cr transition layer in an argon environment at 25-300°C and 0.5-3Pa for 30-90 minutes.
[0073] S8: After the preparation is completed, it is naturally cooled to obtain a LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor for high temperature resistant, corrosion resistant and radiation resistant fasteners.
[0074] Table 1 is the parameter settings corresponding to Example 1
[0075]
[0076] Example 2
[0077] In this embodiment, a high-temperature LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion-resistant and radiation-resistant fasteners and a preparation method thereof are provided. By adjusting the target substrate distance, power supply power, sample preparation temperature, ambient gas type, air pressure, sample preparation time, modulation cycle, number of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating layers, etc., LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensors with different high-temperature stability, corrosion resistance, and radiation resistance can be obtained.
[0078] Combination Figure 2 , piezoelectric coating was deposited on Ti6Al4V titanium alloy bolts, and the corrosion resistance of the coating was verified.
[0079] S1: Plasma beam cleaning substrate: Using 99.99% pure Cr target, the target material Ti6Al4V titanium alloy bolt spacing was adjusted to 140mm, and the surface of the Ti6Al4V titanium alloy bolt was plasma etched at 200℃, 0.8Pa argon environment, substrate bias 150V, duty cycle 80%, cathode current 100A, and the etching time was 10 minutes.
[0080] S2: Deposition of Cr bonding layer: After etching, a 99.99% pure Cr target was used, the target bolt spacing was adjusted to 70 mm, the power supply was set to 700 W, and a 0.7 μm thick Cr bonding layer was deposited on the surface of the Ti6Al4V titanium alloy bolt in an environment of 150 ° C and 1.5 Pa Ar for 10 minutes.
[0081] S3: Deposition of AlN high-temperature diffusion barrier layer: After the deposition of the Cr bonding layer, a 99.99% pure Al target was used, the target bolt spacing was adjusted to 60 mm, the power supply was set to 900 W, the sample preparation room temperature was set to 250 ° C, 2.5 Pa Ar, N2 mixed gas was introduced, and the Ar / N2 ratio was 1:1. An AlN high-temperature diffusion barrier layer with a thickness of about 2 microns was deposited on the surface of the Cr bonding layer for 120 minutes.
[0082] S4: Deposition of LiNbO3 / LiTaO3 piezoelectric functional layer: After the deposition of the AlN high-temperature diffusion barrier layer, use 99.99% pure LiTaO3 target and LiNbO3 target, adjust the target bolt spacing to 60mm, set the power supply to 900W, the sample preparation room temperature to 250℃, introduce 2.5Pa Ar and O2 mixed gas, Ar / O2 ratio 1:1, first deposit the LiTaO3 coating, then deposit the LiNbO3 coating, when the fastener rotates to the front of the LiTaO3 target, stay for 30 minutes, form a 1 micron thick single-layer LiTaO3 coating, when the fastener rotates to the front of the LiNbO3 target, stay for 30 minutes, form a 1 micron thick single-layer LiNbO3 coating, the fastener rotates continuously, and 10 pairs of LiNbO3 / LiTaO3 piezoelectric functional layers are deposited on the surface of the AlN layer, with a total thickness of about 20 microns, for 600 minutes.
[0083] S5: Deposition of Cr electrode bonding layer / protective layer: After the deposition of the LiNbO3 / LiTaO3 piezoelectric functional layer, a 99.99% pure Cr target was used, the target bolt spacing was adjusted to 70mm, the power supply was set to 700W, and a Cr electrode bonding layer / protective layer with a thickness of about 20 microns was deposited on the LiNbO3 / LiTaO3 surface in an argon environment of 150°C and 1.5Pa for 100 minutes.
[0084] S6: After the preparation is completed, it is naturally cooled to obtain a LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor for high temperature resistant, corrosion resistant and radiation resistant fasteners.
[0085] S7: Conduct corrosion resistance test on the piezoelectric coating and the bolt as a whole, use 5% sodium chloride solution spray to conduct corrosion test, set the corrosion time to 500h, and measure the ultrasonic signal of the coating before and after corrosion.
[0086] Ultrasonic signals of coatings before and after corrosion Figure 2 , Figure 2 Figure 8 is the ultrasonic signal of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating before corrosion, and Figure 9 is the ultrasonic signal of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating after corrosion. The signal of LiNbO3 / LiTaO3 nanocomposite piezoelectric coating before annealing is 1.5V, and the signal after corrosion in 5% sodium chloride solution for 200h is 1.7V, indicating that 5% sodium chloride solution does not destroy the piezoelectric properties of the coating, and the LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor has good corrosion resistance.
[0087] Table 2 shows the parameter settings corresponding to Example 2
[0088]
[0089] Embodiment 3:
[0090] Combination Figure 3 , depositing coatings on Inconel superalloy M9 bolts to verify high temperature stability.
[0091] S1: Plasma beam cleaning substrate: Using 99.99% pure Cr target, the distance between the target material and the chromium-nickel-iron super alloy M9 bolt was adjusted to be between 140 mm. In an argon environment of 200°C and 0.8 Pa, the substrate bias was 200 V, the duty cycle was 90%, and the cathode current was 100 A. The surface of the Ti6Al4V titanium alloy bolt was plasma etched for 15 minutes.
[0092] S2: Deposition of Cr bonding layer: as in Example 2.
[0093] S3: Depositing an AlN high temperature diffusion barrier layer: The parameters are set as in Example 2, and an AlN high temperature diffusion barrier layer with a thickness of about 5 μm is deposited on the surface of the Cr bonding layer for 300 minutes.
[0094] S4: Deposition of LiNbO3 / LiTaO3 piezoelectric functional layer: Parameter settings and the first nine pairs of LiNbO3 / LiTaO3 piezoelectric coatings are as in Example 2. In order to better improve the high-temperature oxidation resistance and structural stability of the coating, the last layer of LiNbO3 coating will be thickened to 2 microns. There are 10 pairs of LiNbO3 / LiTaO3 piezoelectric functional layers with a total thickness of about 21 microns, and the duration is 630 minutes.
[0095] S5: Deposition of Cr electrode bonding layer / protective layer: The parameters are set as in Example 2, and a Cr electrode bonding layer / protective layer with a thickness of about 2 μm is deposited on the surface of LiNbO 3 / LiTaO 3 for 100 minutes.
[0096] S6: Deposition of Ag / Cr transition layer: After the deposition of Cr electrode bonding layer / protective layer, Ag 0.3 Cr 0.7 Mix the target, adjust the target bolt spacing to 70 mm, set the power supply to 700 W, and deposit a 1.5 μm thick Ag / Cr transition layer on the surface of the Cr layer in an argon environment at 150 ° C and 1.5 Pa for 10 minutes.
[0097] S7: Deposition of Ag electrode layer: After the deposition of the Ag / Cr transition layer, a 99.99% pure Ag target was used, the target bolt spacing was adjusted to 40 mm, the power supply was set to 700 W, and a Ag electrode layer with a thickness of about 20 microns was deposited on the surface of the Ag / Cr transition layer in an argon environment at 150°C and 1.5 Pa for 90 minutes.
[0098] S8: After the preparation is completed, it is naturally cooled to obtain a LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor for high temperature resistant, corrosion resistant and radiation resistant fasteners.
[0099] High-temperature annealing experiments were carried out on the ultrasonic film and the bolt as a whole. Annealing was carried out under different temperature conditions (100℃, 200℃, 300℃, 400℃, 500℃, 600℃, 700℃, and 800℃). The annealing time at 100℃-600℃ was set to 500 hours, 700℃ was set to 100 hours, and 800℃ was set to 10 hours. The ultrasonic signals of the coating before and after annealing were measured.
[0100] Ultrasonic signals of coatings before and after annealing Figure 3 It can be seen that the ultrasonic signal of the coating has little fluctuation. The highest signal is 1.5V and the lowest signal is 1.23V, with a difference of only 0.27V. After 800℃, it still has a strong ultrasonic signal, indicating that annealing does not destroy the piezoelectric properties of the coating. The LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor has good high-temperature stability.
[0101] Table 3 shows the parameter settings corresponding to Example 3.
[0102]
Claims
1. A high temperature resistant LiNbO3 / LiTaO3 piezoelectric coating sensor for fasteners, characterized in that: Including LiNbO3 / LiTaO3 nanocomposite piezoelectric coating; The LiNbO3 / LiTaO3 nanocomposite piezoelectric coating adopts a gradient multilayer structure, which includes a bonding layer, a high-temperature diffusion barrier layer, a piezoelectric functional layer, a protective layer, a transition layer and an electrode layer from the inside to the outside; wherein the bonding layer is a pure metal Cr layer, the high-temperature diffusion barrier layer is an AlN layer, the piezoelectric functional layer is a LiNbO3 / LiTaO3 nanomultilayer film, the protective layer is a Cr layer, the transition layer is an Ag / Cr layer, and the electrode layer is Ag; After the deposition of the AlN high-temperature diffusion barrier layer is completed, the LiTaO3 target and the LiNbO3 target are turned on at the same time, and a 1.5-4Pa Ar and O2 mixed gas is introduced, and the Ar / O2 ratio is between 0.1-9; when the fastener rotates in front of the LiTaO3 target, it stays for 30-90 minutes to form a LiTaO3 coating; when the fastener rotates in front of the LiNbO3 target, it stays for 30-90 minutes to form a LiNbO3 coating, and the fastener rotates continuously to form 5-20 pairs of LiNbO3 / LiTaO3 coatings on its surface, thereby preparing a nano multilayer composite piezoelectric functional coating.
2. The high temperature resistant LiNbO3 / LiTaO3 piezoelectric coating sensor for fasteners according to claim 1, characterized in that: The high temperature resistant LiNbO3 / LiTaO3 nanocomposite piezoelectric coating sensor for fasteners has a total thickness of 25-70 microns and includes an Ag electrode layer.
3. The high temperature resistant LiNbO3 / LiTaO3 nanocomposite piezoelectric coating for fasteners according to claim 2, characterized in that: The thickness of the Cr bonding layer is 0.5-1 micron; The thickness of the AlN layer high temperature diffusion barrier layer is 3-5 microns; The thickness of the piezoelectric functional layer is 10-20 microns, and the piezoelectric functional layer is a c-axis oriented LiNbO3 / LiTaO3 nano-multilayer film, wherein the thickness of the LiNbO3 single layer is 0.5-2 microns, the thickness of the LiTaO3 single layer is 0.5-2 microns, the modulation period is 1-4 microns, and the number of LiNbO3 / LiTaO3 layers is between 5-20; The thickness of the Cr electrode bonding layer / protective layer is 0.5-20 microns; The thickness of the Ag / Cr transition layer is 1-2 microns; The thickness of the Ag electrode layer is 10-20 microns.
4. A method for preparing a high temperature resistant LiNbO3 / LiTaO3 piezoelectric coating sensor for a fastener as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Plasma cleaning substrate: using 99.99% pure Cr target, adjusting the target fastener spacing between 100-200mm, in 25-300℃, 0.5-2Pa argon environment, substrate bias 100-200V, duty cycle 40-90%, cathode current 80-150A, plasma etching the fastener surface, etching time 5-20 minutes; S2: Deposition of Cr bonding layer: After etching, use a 99.99% pure Cr target, adjust the target fastener spacing between 40-100mm, set the power supply power between 500-1000W, and deposit a Cr bonding layer on the fastener surface in an argon environment of 25-300℃ and 0.5-3Pa for 5-20 minutes; S3: Deposition of AlN high temperature diffusion barrier layer: After the deposition of the Cr bonding layer, a 99.99% pure Al target is used, the target fastener spacing is adjusted to 40-100 mm, the power supply is set to 500-1000 W, the sample preparation room temperature is set to 100-300 ° C, 1.5-4 Pa Ar, N2 mixed gas is introduced, and the Ar / N2 ratio is between 0.1-9, and the AlN high temperature diffusion barrier layer is deposited on the surface of the Cr bonding layer for 200-300 minutes; S4: Deposition of LiNbO3 / LiTaO3 piezoelectric functional layer: After the AlN layer is deposited, a 99.99% pure LiTaO3 target and a LiNbO3 target are used, the target fastener spacing is adjusted to be between 40-100 mm, the power supply is set to be between 500-1000 W, and the sample preparation room temperature is set to be between 150-300 ° C, and the LiNbO3 / LiTaO3 piezoelectric functional layer is deposited on the surface of the AlN layer; S5: Deposition of Cr electrode bonding layer / protective layer: After the deposition of LiNbO3 / LiTaO3 piezoelectric functional layer, a 99.99% pure Cr target is used, the target fastener spacing is adjusted to 40-100mm, the power supply is set to 500-1000W, and the Cr electrode bonding layer / protective layer is deposited on the surface of LiNbO3 / LiTaO3 in an argon environment of 25-300℃ and 0.5-3Pa for 5-240 minutes; S6: Deposition of Ag / Cr transition layer: After the deposition of the Cr electrode bonding layer / protective layer, a AgCr mixed target is used, the ratio of Ag to Cr is between 1:5 and 5:1, the target fastener spacing is adjusted to be between 40-100mm, the power supply power is set to be between 500-1000W, and the Ag / Cr transition layer is deposited on the surface of the Cr layer in an argon environment of 25-300℃ and 0.5-3Pa for 5-20 minutes; S7: Deposition of Ag electrode layer: After the deposition of the Ag / Cr transition layer, a 99.99% pure Ag target is used, the target fastener spacing is adjusted to be between 30-60 mm, the power supply is set to be between 500-1000 W, and the Ag electrode layer is deposited on the surface of the Ag / Cr transition layer in an argon environment at 25-300 ° C and 0.5-3 Pa for 30-90 minutes; S8: After the preparation is completed, it is naturally cooled to obtain a high temperature resistant LiNbO3 / LiTaO3 piezoelectric coating sensor for corrosion resistant and radiation resistant fasteners.
5. The method for preparing the high temperature resistant LiNbO3 / LiTaO3 piezoelectric coating sensor for fasteners according to claim 4, characterized in that: In the step S1, the substrate includes an experimental substrate and an industrial substrate. The experimental substrate is a single crystal silicon wafer or a stainless steel wafer, which is used to characterize the coating thickness, crystal structure, elemental composition and coating bonding strength; the industrial substrate is a Ti6Al4V titanium alloy bolt, an Inconel 718 bolt, a stainless steel bolt, and a nut, a stud, a screw, a washer, a pin, a rivet, and a welding nail, which is used to measure ultrasonic signals and test the piezoelectric properties, high temperature stability, corrosion and radiation resistance of the coating in actual applications.
6. The method for preparing the high temperature resistant LiNbO3 / LiTaO3 piezoelectric coating sensor for fasteners according to claim 5, characterized in that: After the deposition of the AlN high-temperature diffusion barrier layer is completed, the LiTaO3 coating is deposited first, and then the LiNbO3 coating is deposited. The outermost layer of the LiNbO3 / LiTaO3 nanocomposite piezoelectric coating is also LiNbO3; the LiNbO3 coating is located on the surface, and uses its own oxide characteristics to protect the piezoelectric coating from oxidation, thereby improving its high-temperature stability and radiation resistance, and enhancing the coating's ability to resist protons and gamma radiation.
Citation Information
Patent Citations
Temperature-resistant and wear-resistant AlCrN / AlScN nano-composite piezoelectric coating for intelligent bolt and preparation method of AlCrN / AlScN nano-composite piezoelectric coating
CN113293355A
AlN / AlScN nano-composite piezoelectric coating for high-temperature-resistant fastener and preparation method thereof
CN113584443A